From the National Context to its Margins: When the World Used Literature to Respond to the Great War - Toby Garfitt; Nicolas Bianchi (Studies in 20th & 21st Century Literature, 2017)
By shedding light on some original responses to the Great War that are today hardly known, and by asking the same questions of many works written in contexts which were radically different, this STTCL special issue advocates for a genuinely comparative approach to this literature. Born in a context of nationalist withdrawal, these cultural objects also had a paradoxically wide circulation (due to early translations, commentaries, literary reactions, and so on), which is why study of these apparently isolated writers is so valuable.
Keywords: First World War; Literature